Arrhenius Equation for Modeling Feedyard Ammonia Emissions Using Temperature and Diet Crude Protein. Issue 3 (1st May 2013) - Todd, Richard W.; Cole, N. Andy; Waldrip, Heidi M.; Aiken, Robert M.
Abstract : Temperature controls many processes of NH3 volatilization. For example, urea hydrolysis is an enzymatically catalyzed reaction described by the Arrhenius equation. Diet crude protein (CP) controls NH3 emission by affecting N excretion. Our objectives were to use the Arrhenius equation to model NH3 emissions from beef cattle ( Bos taurus ) feedyards and test predictions against observed emissions. Per capita NH3 emission rate (PCER), air temperature ( T ), and CP were measured for 2 yr at two Texas Panhandle feedyards. Data were fitted to analogs of the Arrhenius equation: PCER = f ( T ) and PCER = f ( T, CP). The models were applied at a third feedyard to predict NH3 emissions and compare predicted to measured emissions. Predicted mean NH3 emissions were within −9 and 2% of observed emissions for the f ( T ) and f (T, CP) models, respectively. Annual emission factors calculated from models underestimated annual NH3 emission by 11% [ f ( T ) model] or overestimated emission by 8% [ f ( T, CP) model]. When T from a regional weather station and three classes of CP drove the models, the f ( T ) model overpredicted annual NH3 emission of the low CP class by 14% and underpredicted emissions of the optimum and high CP classes by 1 and 39%, respectively. The f ( T, CP) model underpredicted NH3 emissions by 15, 4, and 23% for low, optimum, and high CP classes, respectively. Ammonia emission was successfully modeled using T only, but including CP improved predictions. The empirical f ( T ) and f ( T, CP) models can successfully model NH3 emissions in the Texas Panhandle. Researchers are encouraged to test the models in other regions where high‐quality NH3 emissions data are available.